Analysing the Governance Factors for Sustainability in Organisations and Their Inter-Relations - Temel, Melis; Lozano, Rodrigo; Barreiro-Gen, Maria (Frontiers in Sustainability, 2021)
Governance is instrumental to the implementing sustainability into organisations (civil society, companies, and public sector ones). Seven governance factors have been identified to achieve this: vision and mission, policies, reporting, communication, board of directors, department, and person in charge. However, their importance and interrelations are still under-researched. A survey was sent to 5,299 organisations, with 305 responses. The responses were analysed using descriptive statistics, rankings, comparison between organisation types, correlations, and centrality. The results provide the ranking of the factors, where vision and mission, person in charge, and reporting were highest ranked. The results also show that the seven factors are interrelated, albeit some more than others. The research provides a comparison of the rankings and interrelations between the organisation types. Each factor and its relation to other factors can contribute to better governance for sustainability, and better governance can contribute to a more holistic implementation of sustainability in organisations